(untitled) (Research, Society and Development, 2023)
This article aims to understand the impact of the COVID-19 pandemic on the closing and opening of Small Businesses in the Municipality of Itapagipe/MG. For that, a bibliographical and documentary research was carried out, identifying data in primary and contemporary sources. A quantitative approach was used for data analysis and interpretation. The data used refer to the Closing and Opening of Small Businesses in the State of Minas Gerais, the Microregion of Frutal/MG and the Municipality of Itapagipe/MG, from 2012 to 2022. The analysis of the data made it possible to verify that there are similarities in the trend of growth observed in the data on the opening of Small Businesses, but the same cannot be considered regarding the closing of these businesses in the regions and in the analyzed period.